A Body of Texts: Memento and Mētis. Issue 1 (1st June 2021) - Tirrell, Jeremy
Abstract: This article applies materialist rhetoric to Christopher Nolan's 2000 neo-noir film Memento and positions its protagonist Leonard Shelby, a man with a brain injury that prevents him from making new memories, as a figure of mētis : a classical concept addressing the cunning ability to respond to the contingent, kairotic moment by engaging situations through a reciprocal process of change. As evidence for its assertion, the article examines Leonard's relationship to his shifting bodily archive of tattoos, handwritten notes, and annotated Polaroid pictures. It also aligns him with the ancient hero Odysseus and the sophistic rhetorician Gorgias, two classical exemplars of mētis . Leonard's mētic existence informs how contemporary selves emerge from networks of objects both physical and virtual.